Impact Of The Covid-19 Pandemic On Glycemic Control In Childhood Type 1 DM Patients - Toni Kurniawan; Eka Agustia Rini; Asrawati Asrawati (Eduvest - Journal of Universal Studies, 2024)
There has been an increase in cases of diabetic ketoacidosis in children aged 1-14 years from 73% in 2019 to 83% in 2020 during the COVID-19 pandemic. An increase in acute complications of type-1 DM can occur due to lack of compliance with glycemic control and activity restrictions which have the impact of reducing the level of glycemic control in children with type-1 DM. Based on these findings, researchers wanted to know the impact of restrictions on community activities during pandemic on the glycemic control of children with type 1 DM. The aims of this study is to determine the impact of the COVID-19 pandemic on glycemic control through HbA1c parameters in children with type 1 DM. Methods of this research is a cross sectional study with a sample size of 26 patients. Results are The average age of respondents was 15.58 years. More than half of respondents were female (73.1%). The average duration of suffering from type 1 DM was 4.77 years. More than half of the respondents had a history of diabetic ketoacidosis, 53.8%, and all respondents were Health Insurance (BPJS) participants (100%). There was a decrease in HbA1c levels during the pandemic compared to before the pandemic, namely 12.17 ± 2.60 to 10.32 ± 2.21. Statistically, this decrease means that there is an impact of the COVID-19 pandemic on glycemic control through the HbA1c parameter in children with type 1 DM (p<0.05). There was a decrease in HbA1c levels during the pandemic compared to before the pandemic.